2000
DOI: 10.1016/s0194-5998(00)70047-7
|View full text |Cite
|
Sign up to set email alerts
|

Tall Cell Variant: An Aggressive Form of Papillary Thyroid Carcinoma

Abstract: Twenty-four cases of the tall cell variant (TCV), a subset of papillary thyroid carcinoma, were identified in a group of 624 patients with thyroid cancer. All pathology specimens were reviewed, and each patient's carcinoma was categorized according to characteristics on presentation, local recurrence, distant metastases, follow-up, and tumor-related mortality. The TCV group was compared with a historical control group (Mazzaferri and Jhiang: 1355 patients). The TCV group had a statistically higher percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 14 publications
5
26
0
3
Order By: Relevance
“…Mean tumor size was comparable to the tumor size in UV papillary thyroid cancer. Reviewing the data from [3, 810], the TCV patients had a higher rate of extrathyroidal extension (cumulative average of 60.33% patients) and higher rate of distant metastases at diagnosis (cumulative average of 15%). In addition, the cumulative average of lymph node metastases in TCV cases is 58.12% versus 34.5% in UV cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean tumor size was comparable to the tumor size in UV papillary thyroid cancer. Reviewing the data from [3, 810], the TCV patients had a higher rate of extrathyroidal extension (cumulative average of 60.33% patients) and higher rate of distant metastases at diagnosis (cumulative average of 15%). In addition, the cumulative average of lymph node metastases in TCV cases is 58.12% versus 34.5% in UV cases.…”
Section: Resultsmentioning
confidence: 99%
“…The published incidence of TCV is between 3.8% and 10.4% [1, 410]. Unlike the usually good prognosis of usual variant papillary thyroid cancer (UV), TCV histology is generally reported as an independently poor prognostic factor [1, 3, 5, 6, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…The incidence of TCV varies from 1.3% to 13% of all PTC in literature [3, 18, 21, 24]. The variation in reported prevalence was mainly due to the various diagnostic criteria, difficulty in distinguishing TCV from other variants, and less attention paid to this entity at routine pathological examination.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, it has been debated that whether the worse prognosis associated with TCV is attributable to various adverse clinico-pathological parameters or histological type alone. Some studies [7, 18, 41] have shown that TCV histology was not an independent risk factor for thyroid cancer recurrence and death postoperatively, and the most relevant factors being age, tumor size, ex­trathyroidal extension, and TNM stage in multivariate analysis.…”
Section: Prognosismentioning
confidence: 99%
“…TCV PTC is an aggressive tumour characterised by its tall columnar shape, with a height : width ratio of 2-3 : 1 and abundant eosinophilic or oxyphilic cytoplasm [1, 2, 6, 7]. Although a rare occurrence, TCV PTC may transform into anaplastic SCSC.…”
Section: Discussionmentioning
confidence: 99%